Inflammatory niche: Mesenchymal stromal cell priming by soluble mediators - Jauković, Aleksandra (World J Stem Cells, 2020)
Mesenchymal stromal/stem cells (MSCs) are adult stem cells of stromal origin that possess self-renewal capacity and the ability to differentiate into multiple mesodermal cell lineages. They play a critical role in tissue homeostasis and wound healing, as well as in regulating the inﬂammatory microenvironment through interactions with immune cells. Hence, MSCs have garnered great attention as promising candidates for tissue regeneration and cell therapy. Because the inflammatory niche plays a key role in triggering the reparative and immunomodulatory functions of MSCs, priming of MSCs with bioactive molecules has been proposed as a way to foster the therapeutic potential of these cells. In this paper, we review how soluble mediators of the inflammatory niche (cytokines and alarmins) influence the regenerative and immunomodulatory capacity of MSCs, highlighting the major advantages and concerns regarding the therapeutic potential of these inflammatory primed MSCs. The data summarized in this review may provide a significant starting point for future research on priming MSCs and establishing standardized methods for the application of preconditioned MSCs in cell therapy.